Re-Branding UMKM dengan Pendekatan Bisnis Dan Komunikasi Visual dalam Proses Pembelajaran Menggunakan Project Based Learning (Studi Kasus Maestro Pempek) - Prasadhya, Ignatius Bias Galih; Pratiwi, Nugrahaning Esa; Kaitelapatay, Big Greogory (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to provide insight into the concept of digital marketing strategies and visual communication used for product marketing. Service activities are carried out using interview methods and SWOT analysis as well as direct assistance to MSME managers. The results of community service activities produce work through a graphic design approach in the form of changing business names, rebranding logos, Instagram accounts, feed content, catalogs and new packaging designs. Apart from that, this activity can increase the knowledge of MSME players about innovation and digital marketing strategies and is useful in promoting products more widely, so that potential buyers are increasingly interested in buying MSME products